2019
DOI: 10.1002/qua.26055
|View full text |Cite
|
Sign up to set email alerts
|

Moving boundary truncated grid method: Multidimensional quantum dynamics

Abstract: The moving boundary truncated grid (TG) method is used to study wave packet dynamics of multidimensional quantum systems. As time evolves, appropriate Eulerian grid points required for propagating a wave packet are activated and deactivated with no advance information about the dynamics. This method is applied to the Henon-Heiles potential and wave packet barrier scattering in two, three, and four dimensions. Computational results demonstrate that the TG method not only leads to a great reduction in the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…Computational Details. As shown in our previous work, 93 having a high-performance code is the key to overcome the computational overhead and achieve speed acceleration in moving boundary TG calculations. Our implementation of the method 110 is based on a sharedmemory scheme with loop-level OpenMP parallelism.…”
Section: Theoretical Formulationmentioning
confidence: 98%
See 4 more Smart Citations
“…Computational Details. As shown in our previous work, 93 having a high-performance code is the key to overcome the computational overhead and achieve speed acceleration in moving boundary TG calculations. Our implementation of the method 110 is based on a sharedmemory scheme with loop-level OpenMP parallelism.…”
Section: Theoretical Formulationmentioning
confidence: 98%
“…Although decreasing the values of the TG parameters leads to an increase in the total number of the TG points, computational results demonstrated that the computational cost for the TG method still greatly decreases with the dimensionality of the system. 93 Furthermore, as discussed in Section 2.2.4, a switch function can be implemented in the computer program that toggles between the FG and TG modes to ensure the efficiency and accuracy of our TG calculation.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 3 more Smart Citations